Obesity, polycystic ovary syndrome and breastfeeding: an observational study. (7th February 2016) - Joham, Anju E.; Nanayakkara, Natalie; Ranasinha, Sanjeeva; Zoungas, Sophia; Boyle, Jacqueline; Harrison, Cheryce L.; Forder, Peta; Loxton, Deborah; Vanky, Eszter; Teede, Helena J.
Abstract: Introduction: Polycystic ovary syndrome (PCOS) affects 9–21% of reproductive‐age women. The relations between PCOS, body mass index (BMI) and breastfeeding are unclear. Our aim was to examine breastfeeding in women with and without PCOS and the relation with BMI. Material and methods: This is a cross‐sectional study set in the general community. Participants are women, aged 31–36 years, from the Australian Longitudinal Study on Women's Health (ALSWH), a large community‐based study. Data was analyzed from the first child of respondents to Survey five (2009) reporting at least one live born child. Logistic regression analysis was used to examine factors associated with breastfeeding. The main outcome measures studied were breastfeeding initiation and duration and the main explanatory variables included self‐reported PCOS and BMI. Results: Of the 4898 women, 6.5% reported PCOS (95% confidence interval 5.8–7.2%). Median duration of breastfeeding was lower in women reporting PCOS (6 months, range 2–10 months) than in women not reporting PCOS (7 months, range 3–12 months) ( p = 0.001). On multivariable regression analysis, there was no association between PCOS and breastfeeding outcomes. However, being overweight or obese was associated with not initiating breastfeeding and with breastfeeding for less than 6 months, after adjusting for confounders. Conclusions: High BMI is negatively associated with breastfeeding, whereas PCOS status per se does not appear to be related to breastfeeding initiation and duration, after adjusting for BMI.